In defense of a general right to conscientious objection - Gascón Abellán, Marina (EUNOMÍA. Revista en Cultura de la Legalidad, 2018)
Abstract: I advocate here the thesis that there is a general right to conscientious objection based on the freedom of conscience, which means it is possible for a person to invoke conscientious objection to avoid performing a legal obligation even though there is no legal provision expressly recognizing to do so. A general right to conscientious objection cannot be interpreted in absolute terms. Conscientious objection in a particular case can only be accepted if certain requirements are met. I also examine those requirements: particularly the need to hold genuine convictions or religious beliefs and protect public order and the rights of others. Finally, I claim it would be convenient to regulate the most relevant forms of conscientious objection, and some suggestions on the matter will be proposed.
Keywords: Keywords: Freedom of conscience, freedom of thought, conscience and religion, conscientious objection, human rights, public order.; Freedom of conscience; freedom of thought; conscience and religion; conscientious objetion; human rights; public order